The effect of morphological and functional variables on ranking position of professional junior Basque surfers - Fernandez-Lopez, J. R.; Camara, J.; Maldonado, S.; Rosique-Gracia, J. (European Journal of Sport Science, 2013)
The aim of this study was to analyse the association of morphology as well as functional outcomes during a paddling test with ranking position (RP) of competitive junior surfers. Ten male surfers (age, mean 17.60, s=2.06 years) performed a maximum incremental test on a modified ergometer (Ergo Vasa Swim, USA) to determine, per unit of weight, the relative heart rate at lactate threshold (RHRLT) and at onset of blood lactate accumulation (RHROBLA) and the relative power output at LT (RWLT) and at OBLA (RWOBLA). Anthropometrics were weight, height and sum of six skinfolds (subscapular, triceps, supraspinal, abdominal, anterior thigh and calf) and Heath-Carter anthropometric somatotypes. A stepwise multiple regression was constructed to model and predict RP. Surfers shared a relative short stature and light weight, with a broader range of skinfold thickness (174.30, s=0.07 cm; 66.73, s=5.91 kg; 57.03, s=12.29 mm) and mean somatotype was ectomorphic-mesomorph: 2.20-4.36-3.09 (Category 2). Two model equations were possible: (A) RP = - 244.550 RWOBLA+262.787; (B) RP = - 217.028·RWOBLA+31.21·endomorphy + 169.16 with 63.1% and 83% of variance explained, respectively. A hierarchical cluster analysis on the Euclidean distances of the variables in model B also distinguished between upper and lower ranking groups. RWOBLA was more useful than endomorphy, anthropometric measures and also than the other functional outcomes to predict RPs. RWOBLA and endomorphy should be considered important variables that may influence the success of these young competitive surfers.